Application of risk stratification of a family with a history of domestic violence: experience report (Research, Society and Development, 2023)
Family is an institution that needs to be better monitored by health services, to identify the social vulnerabilities presented and subsequent intervention. The objective was to describe the risk stratification of a family with a history of domestic violence. This is an experience report, based on a case study, carried out in Ipueiras - Ceará. The Coelho-Savassi Family Risk Scale (ERF – CS) was used as a family approach tool. The family was classified as nuclear and obtained a score of 19 points, that is, maximum risk (R3). The index case developed a mental disorder due to domestic violence. The health team can act by carrying out home visits, conflict mediation, multidisciplinary care and referral to employment and income generation services. The use of the ERF - CS allows assessing the needs of each family, for the planning and execution of health actions, in order to promote better living conditions.